Funerary megalithism in the south of Beira Interior: architectures, spoils and cultural sequences - Cardoso, João Luís (2020)
In this study, we present the main results obtained during the archaeological survey of a vast area in the south of Beira Interior, in the region of the International Tagus river, followed by the excavation of the most representative and best preserved funerary megalithic monuments. It was possible to identify several types of monuments and to relate these with the artefact findings, and then to develop a model to explain the architectonic succession of funerary megalithic monuments in the region. It was also possible to observe some constructive particularities in some of these monuments, herein summarized.